GAMBARAN STATUS GIZI DAN ASUPAN ZAT GIZI PADA SISWA SEKOLAH DASAR KECAMATAN SUNGAI SEMBILAN KOTA DUMAI - Utari, Lintang Dwi; Ernalia, Yanti; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTSchool-age children need a good nutrition to support learning activities at school. Nutritional intake will affect the concentration of power and intelligence of the child in receiving and absorbing the knowledge gained in school. The purpose of this study was to describe the nutritional status and nutrient intake in children of primary school in Sungai Sembilan, Dumai City. This research is a descriptive study with cross-sectional design. Respondents in this research were 153 boys and 192 girls were calculated BMI by measuring height and weight. Dietary intake assessment done by asking parents to fill the food record. Nutritional status is divided into very thin, thin, normal, obese and very obese, based on anthropometric indices while food intake consists of energy intake, carbohydrate, protein and fat. Children with very poor nutritional status of 3,5%, children with malnutrition status of 3,5%, obese children with nutritional status of 16.5%, the nutritional status of children with very fat 2,6% The majority of children receive the intake deficit Energy 36.5%, 52.2% less carbohydrates, less protein and less fat 41.7 43.5%.Keywords : children of school age, nutritional status, nutrient intake